1996
DOI: 10.1056/nejm199608083350602
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Regimens for the Treatment ofMycobacterium aviumComplex Bacteremia in AIDS: Rifabutin, Ethambutol, and Clarithromycin versus Rifampin, Ethambutol, Clofazimine, and Ciprofloxacin

Abstract: In patients with AIDS and M. avium complex bacteremia, treatment with the three-drug regimen of rifabutin, ethambutol, and clarithromycin leads to resolution of the bacteremia more frequently and more rapidly than treatment with rifampin, ethambutol, clofazimine, and ciprofloxacin, and survival rates are better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
1
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(90 citation statements)
references
References 26 publications
4
79
1
6
Order By: Relevance
“…Curiously, similar to our present findings, IL-10 seems not to underlie the susceptibility to tuberculosis in the mouse model (52). Since long-term treatment of both tuberculosis and M. avium infection with the appropriate conventional chemotherapy usually leads to severe side effects (11,12), the possibility of improving antimycobacterial activity of current antibiotics by interfering with IL-10 signaling may help circumvent these problems.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Curiously, similar to our present findings, IL-10 seems not to underlie the susceptibility to tuberculosis in the mouse model (52). Since long-term treatment of both tuberculosis and M. avium infection with the appropriate conventional chemotherapy usually leads to severe side effects (11,12), the possibility of improving antimycobacterial activity of current antibiotics by interfering with IL-10 signaling may help circumvent these problems.…”
Section: Discussionsupporting
confidence: 85%
“…Long-term treatment with macrolides such as clarithromycin, which is highly effective in the treatment of MAC infections (4,5), leads to the emergence of resistant forms (6 -8), which can be prevented by combining at least two or three drugs (9,10). However, this in turn can lead to severe side effects (11,12). Ways to shorten therapeutical courses as well as increasing efficacy of the treatment are thus needed.…”
mentioning
confidence: 99%
“…The drug was shown to be even more bactericidal than isoniazid when tested in a mouse model of tuberculosis chemotherapy (2). For reasons that are not well documented, clofazimine was not advanced for the treatment of human tuberculosis but was used for the treatment of leprosy and later, unsuccessfully, for the treatment of Mycobacterium avium complex infection in patients with AIDS (3,4). The unfortunate development of multidrug-and extensively drug-resistant tuberculosis has kindled a worldwide push for the development of new therapy options for this disease, including a renewed interest in clofazimine (5).…”
mentioning
confidence: 99%
“…Clinical trials have supported the superiority of clarithromycin, ethambutol, and rifabutin over rifampicin, ethambutol, clofazimine, and ciprofloxacin (56). A compara- Uncorrected Proof Copy 258 Gillespie tive trial suggested that lower doses of rifabutin (300 mg daily) together with ethambutol are more effective than a four-drug regimen of rifampicin, ethambutol, clofazimine, and ciprofloxacin, still retaining much of the activity of clarithromycin (1000 mg twice daily) and rifabutin (600 mg daily) doses (56).…”
Section: Management Of Disseminated Infection In Hiv-seropositive Patmentioning
confidence: 99%